Base‐Catalyzed NN Bond Cleavage of Hydrazones: Synthesis of α‐Amino Ketones. Issue 5 (5th March 2014) - Tang, Hai‐Tao; Zhou, Yun‐Bing; Zhu, Yu; Sun, Hong‐Chao; Lin, Min; Zhan, Zhuang‐Ping
Abstract An efficient Cs2CO3‐promoted synthesis of α‐amino ketones using hydrazines, aldehydes, and α‐haloketones as starting materials through a cascade condensation/nucleophilic substitution/NN bond cleavage route is developed. The carbonyl group plays a key role in this novel NN bond cleavage process.